Promoting speaking via the teaching of listening in EFL intermediate classes at CEG 2 Adjarra, Republic of Benin: a linguistic perspective - LOKO, Djima Crépin (My University, 2023)
The aim of this research work is to uncover the impact of listening skills and that of listening practice in the improvement of learners’ oral performance. Hence, the present work contributes to help EFL teachers to find learners’ deficiencies in speaking by showing the inter relationship and the interdependence of both skills on each other. The methods used to collect data are quantitative and qualitative and consist in collecting information from thirteen (13) EFL teachers and eighty (80) EFL learners through the means of interviews and questionnaires at CEG 2 Adjarra. Results show that all of the respondents believe that the listening skills and listening activities, specifically, constitute an important source that can enable EFL learners to develop their oral production. However, this study has revealed that listening practice happens not to be at the centre of attention inside the class as it should be. This negligence causes learners not to have enough contact with the language and, as a matter of fact, makes them unable to speak it fluently. So, some solutions are proposed to help teachers to integrate more listening activities in their teaching so as to better learner speaking skills.
Keywords: Listening; speaking; language proficiency; phonetics; Competency-Based Approach